Обґрунтування умов вивчення й упровадження досвіду провідних країн світу в практику роботи вищих навчальних закладів України - Танько, Євгенія; Tanko, Yevgeniya (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті досліджено проблеми розвитку вищої освіти в контексті міжнародної співпраці. Обґрунто-вано умови необхідності вивчення й поширення досвіду провідних країн світу, зокрема Великобританії, у галузі вищої освіти для забезпечення сталого розвитку ВНЗ України. До таких умов віднесено інноваційну освітню політику, інтеграцію в європейський освітній і науковий простір, нове соціальне замовлення суспільства щодо підготовки фахівців у ВНЗ, гуманізацію навчального процесу, забезпечення якості освіти. The article is dedicated to the problems of development of higher education in the context of international cooperation. It was grounded the conditions of necessity of studying and dissemination of experience of the leading countries of the world, especially Great Britain, in the sphere of higher education for guaranteeing of stable development of higher educational establishements of Ukraine. Such conditions are the following: innovative educational politics, integration into European educational and scientific space, new social order of society in preparation of specialists for higher educational establishments, humanization of educational process, providing of quality of education.
Grounding of Conditions of Studying and Implementation of Experience of the Leading Countris of the World Into Practice of Work of Educational Institutions of Ukraine
Keywords: умова; освітня політика; загальноєвропейський освітній простір; соціальне замовлення; гуманізація освіти; якісна освіта; condition; educational politics; general European educational spcace; social order; humanization of education; education of high quality